Biomechanical simulation of temporomandibular joint replacement (TMJR) devices: a scoping review of the finite element method. Issue 8 (August 2018) - Rodrigues, Y.L.; Mathew, M.T.; Mercuri, L.G.; da Silva, J.S.P.; Henriques, B.; Souza, J.C.M.
Abstract: The aim of this study was to perform a literature review on the use of finite element modeling (FEM) for the evaluation of the biomechanical behavior of temporomandibular joint replacement (TMJR) devices. An electronic search of online medical and scientific literature database was conducted using selected search terms. The search identified 307 studies, of which 19 were considered relevant to this study. Of the 19 selected studies, 10 (52.6%) investigated the influence of geometry and fixation methods, while two (10.5%) evaluated the behavior of artificial condyle–fossa structures. The TMJR devices assessed in these studies included TMJ Inc. (aka Christensen; 63.2%), Zimmer Biomet (15.7%), Stryker (10.5%), and a theoretical intramedullary condylar component (5.3%); 26.3% of the studies evaluated custom TMJR devices. Such studies provided important data on the distribution of strain and stress through TMJR structural components and surrounding bone by using different software systems and methods. The mean stress values were lower on a custom TMJR condyle–ramus component and the supporting bone than on the stock device. FEM proved to be an accurate and valuable biomechanical simulation tool for studying the current TMJR devices and should be considered a useful tool for the improvement and development of future joint replacement devices.